Conference Record of the Twenty-Ninth IEEE Photovoltaic Specialists Conference, 2002.
DOI: 10.1109/pvsc.2002.1190480
|View full text |Cite
|
Sign up to set email alerts
|

On combining surface and bulk passivation of SiN/sub x/:H layers for mc-Si solar cells

Abstract: A route, as followed by ECN, is described for development of Si N,:H layers deposited by microwave (MW) PECVD. which are suited for surface and bulk passivation of moSi solar cdls. First research was focussed on surface passivation and this resulted in the development of SIN layers that were Si-rich and where the hydrogen is mainly bonded to Silicon atoms. A disadvantage of such Si-rich layers is their large absorption at shorter wavelengths, which make them unsuitable as front side AR coatings. Further. these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…[22][23][24] The in-line system at ECN, which consists of loadlock and preheating and cooling compartments, is capable of processing 150 wafers (10ϫ10 cm 2 size͒ per hour in a continuous process. The plasma source is situated in the middle compartment of the reactor and consists of a quartz tube with a Cu antenna inside.…”
mentioning
confidence: 99%
“…[22][23][24] The in-line system at ECN, which consists of loadlock and preheating and cooling compartments, is capable of processing 150 wafers (10ϫ10 cm 2 size͒ per hour in a continuous process. The plasma source is situated in the middle compartment of the reactor and consists of a quartz tube with a Cu antenna inside.…”
mentioning
confidence: 99%
“…However, for thicker LPC-Si absorbers, additional hydrogen passivation is imperative to reduce recombination in the bulk as also observed for solar cells using multicrystalline wafers. 69 …”
Section: Discussionmentioning
confidence: 99%
“…This high mass density is identical to the optimal value reported for parallel plate PECVD at which the best bulk passivation is observed. 39 A detailed study of the hydrogen behavior on the applied high density HWCVD SiN x coatings was conducted, 45 and revealed that in all layers the hydrogen release mainly originated from the N-H bond configuration. It is remarkable that in both experiments the IQE value for wavelength smaller than 600 nm the cells, with HWCVD SiN x , was significantly better.…”
Section: Discussionmentioning
confidence: 99%
“…This difference is caused by unoptimized cell processing parameters for the cells with HW deposited SiN x , such as firing conditions. For example, HW deposited SiN x has a higher mass density 39,40 and may therefore necessitate different firing settings for optimization of the FF. In addition the thickness homogeneity of the layers could play a role here, since the cells are 6Á5 Â 6Á5 cm 2 , whereas the homogeneous zone in our experimental HW reactor is 5 Â 5 cm 2 .…”
Section: Hwcvd Sin X On Ecn Mc-si Solar Cellsmentioning
confidence: 99%